Association between changes in bodyweight and cardiovascular disease risk factors among obese Japanese patients with type 2 diabetes. Issue 9 (29th April 2022) - Yoshimura, Ran; Nakagami, Tomoko; Hasegawa, Yukiko; Oya, Junko; Babazono, Tetsuya
Abstract: Aims/Introduction: We aimed to assess the association between bodyweight reduction and cardiovascular disease risk factors, and to identify the minimum bodyweight reduction associated with significant improvement in cardiovascular disease risk factors among obese Japanese patients with type 2 diabetes. Materials and Methods: The cohort comprised 1, 753 patients with type 2 diabetes and body mass index ≥25 kg/m 2, who visited our clinic between 2013 and 2016. Multivariable linear regression analysis was carried out to assess the relationship between bodyweight changes and glycated hemoglobin A1c, serum lipids and blood pressure. Analyses of covariance were carried out to compare mean changes in cardiovascular disease risk factors across six groups of bodyweight change, <−5%, −5% to <−3%, −3% to <−1%, −1% to <1% (reference), 1% to <3% and ≥3%. Results: Log‐transformed bodyweight change had a significantly positive relationship with log‐transformed glycated hemoglobin A1c, triglycerides, low‐density lipoprotein cholesterol and systolic blood pressure changes, and a negative relationship with high‐density lipoprotein cholesterol, after adjusting for sex, age, duration of diabetes, body mass index, use of glucose‐lowering, lipid‐lowering and antihypertensive agents, and changes in the use of these medications. A mean change in glycated hemoglobin A1c was significantly improved only in the <−5% group compared with the reference. Mean changes in triglycerides were improved in all groups, and significantly in the <−5% group. Conclusions: Bodyweight change was significantly associated with cardiovascular disease risk factor changes, and >5% bodyweight reduction was associated with improved glycated hemoglobin A1c. Abstract : Body weight change was significantly associated with cardiovascular disease risk factor changes, and more than 5% body weight reduction was associated with improved glycated hemoglobin A1c.